Dermoscopy of Melanoma and Non-melanoma Skin Cancers - Kato, Junji; Horimoto, Kohei; Sato, Sayuri; Minowa, Tomoyuki; Uhara, Hisashi (Frontiers in Medicine, 2019)
Dermoscopy is a widely used non-invasive technique for diagnosing skin tumors In melanocytic tumors, e.g. melanoma and basal cell carcinoma, the effectiveness of dermoscopic examination has been fully established over the past two decades. Moreover, dermoscopy has been used to diagnose non-melanocytic tumors. Here, we review novel findings from recent reports concerning dermoscopy of melanoma and non-melanoma skin cancers including basal cell carcinoma, sebaceous carcinoma, actinic keratosis, Bowen’s disease, squamous cell carcinoma, Merkel cell carcinoma, extramammary Paget’s disease, and angiosarcoma.